Vexibia Alopecroides - How to New Source for the Synthesis of Physiologically Active Substances Used in Medicine - S.S. Yusupova; D.K. Kholmurodova; D.Sh. Kiyamova (Global Scientific Publishing, 2023)
This work is devoted to the isolation of Vexibia alopecia des from the Fabacea family e physiologically active flavonoids and the possibility of synthesizing drugs used in medicine on their basis. As a result of the work, a flavonoid was isolated – in exibinol, its structure and properties were studied, and identified by IR, UV, PMR, NMR 13 methods of analysis.
Keywords: Flavonoids; soforamine; matrine; cytosine